PERSEPSI PARA STAKEHOLDER TENTANG NILAI PENTING WARISAN BUDAYA MEGALITIK DI KAWASAN LEMBAH BADA - Hidayat, Romi; Tanudirjo, Daud Aris (Jambura History and Culture Journal, 2024)
The Bada Valley area has high-value cultural and natural wealth that needs to be preserved and managed properly. For this reason, understanding the significant values of its cultural and natural resources is important. Up to now, the significant value of cultural heritage in this area has often been debated, because it is resulted from an Authorized Heritage Discourse, in which the values are determined solely by the authority and prioritizes the material elements of the cultural heritage. This discourse is no longer relevant today. This paper will discuss the results of significant values derived from a different approach, namely the multistakeholder perspective. The importance of cultural heritage is determined based on the views of the identified stakeholders. This descriptive qualitative research focused on Lengkeka and Kolori villages, which were selected by purposive sampling. The results of this study show that there is a diversity of significant values of cultural heritage. Differences in seeing significant values need to be accommodated in good management and preservation, so that each party can play a role in management and obtain benefit equitably.